2019
DOI: 10.1039/c9ra00308h
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient methyldiethanolamine (MDEA) removal and light naphtha purificationviasynergistic effect of molecular sieves and fixed adsorption bed

Abstract: The adsorption effect of 13X on MDEA in light naphtha was studied and compared with NKA-9 and silica gel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…However, solvent naphtha and MDEA are fully mixed in the lye tank during the desulfurization process. After MDEA absorbs H 2 S in the oil, the solvent naphtha comes out from the top of the tank by layering and separation treatment, entraining a small amount of MDEA drops, which causes the pH of the solvent naphtha to increase from around 6.8 to around 9.7 . This solvent naphtha is used to process gasoline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, solvent naphtha and MDEA are fully mixed in the lye tank during the desulfurization process. After MDEA absorbs H 2 S in the oil, the solvent naphtha comes out from the top of the tank by layering and separation treatment, entraining a small amount of MDEA drops, which causes the pH of the solvent naphtha to increase from around 6.8 to around 9.7 . This solvent naphtha is used to process gasoline.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, two-phase separation methods include adsorption, centrifugal separation, gravity sedimentation, membrane separation, and extraction . Zhang et al used a fixed adsorption bed system with a molecular sieve (13X) to remove MDEA from light naphtha and investigated the adsorption mechanism of 13X. Peng et al made a novel mesoporous material and conducted adsorption experiments at 298.15 K and found that this new material showed promise as a separation adsorbent.…”
Section: Introductionmentioning
confidence: 99%